Structural and spectroscopic effects of Li+ substitution for Na+ in LixNa1-xCaLa0.5Er0.05Yb0.45(MoO4)3 upconversion scheelite-type phosphors - Lim, Chang Sung; Aleksandrovsky, Aleksandr S.; Molokeev, Maxim S.; Oreshonkov, Aleksandr S.; Atuchin, Victor V. (Crystals)
New triple molybdates LixNa1−xCaLa0.5(MoO4)3:Er3+0.05/Yb3+0.45 (x = 0, 0.05, 0.1, 0.2, 0.3) were manufactured successfully using the microwave-assisted sol-gel-based technique (MAS). Their room-temperature crystal structures were determined in space group I41/a by Rietveld analysis. The compounds were found to have a scheelite-type structure. In Li-substituted samples, the sites of big cations were occupied by a mixture of (Li, Na, La, Er, Yb) ions, which provided a linear cell volume decrease with the Li content increase. The increased upconversion (UC) efficiency and Raman spectroscopic properties of the phosphors were discussed in detail. The mechanism of optimization of upconversion luminescence upon Li content variation was shown to be due to the control of excitation/energy transfer channel, while the control of luminescence channels played a minor role. The UC luminescence maximized at lithium content x = 0.05. The mechanism of UC optimization was shown to be due to the control of excitation/energy transfer channel, while the control of luminescence channels played a minor role. Over the whole spectral range, the Raman spectra of LixNa1−xCaLa0.5(MoO4)3 doped with Er3+ and Yb3+ ions were totally superimposed with the luminescence signal of Er3+ ions, and increasing the Li+ content resulted in the difference of Er3+ multiple intensity. The density functional theory calculations with the account for the structural disorder in the system of Li, Na, Ca, La, Er and Yb ions revealed the bandgap variation from 3.99 to 4.137 eV due to the changing of Li content. It was found that the direct electronic transition energy was close to the indirect one for all compounds. The determined chromaticity points (ICP) of the LiNaCaLa(MoO4)3:Er3+,Yb3+ phosphors were in good relation to the equal-energy point in the standard CIE (Commission Internationale de L'Eclairage) coordinates.